Image analysis of Gray Matter alterations and White Matter lesions in Multiple Sclerosis - Singh, Sonika (2021)
Multiple Sclerosis (MS) is a frequently disabling neurological disease affecting young adults. The disease has been characterized by recurrent areas of focal inflammation (plaques) in the CNS giving rise to episodic neurological signs and symptoms. Helminth-associated immunoregulation has been investigated by the utilization of controlled hookworm infection in MS. Many studies have reported brain atrophy in patients with MS. This has been demonstrated as a major factor for physical and cognitive impairment in MS. In this thesis, I present our studies using immunomodulation, coordinate-Based Meta-Analysis (CBMA), Meta-Analysis of Networks (CBMAN), and Meta-Regression and voxel based morphometry (VBM) to study disease activity in MS. 1) For a Randomized Double-Blinded Placebo-Controlled Trial, we examined the effect of hookworm treatment on white matter (WM) disease activity. 2) Localised grey matter (GM) Atrophy in Multiple Sclerosis and Clinically Isolated Syndrome (CIS) was investigated by Coordinate-Based Meta-Analysis, Meta-Analysis of Networks, and Meta-Regression of Voxel-Based Morphometry Studies to reveal the significantly consistent regions and networks of GM atrophy in MS or CIS. 3) A further VBM was conducted in the revealed clusters to investigate the difference in GM atrophy between hookworm and placebo arms of the clinical trial, during the course of intervention.